A First Amendment profile of the Supreme Court - Smith, Craig R. (John Cabot University Press ; Distributed by University of Delaware Press, 2011)
"A First Amendment Profile of the Supreme Courti focuses on the nine justices of the United States Supreme Court and determines their frames for assessing First Amendment cases. In each of the chapters, a justice will be profiled in terms of his or her claims during the nomination hearings and the positions they have taken in significant Supreme Court decisions. The object of these chapters is to provide a rhetorical frame that each of these justices would find appealing regarding First Amendment case law"--